Morphometric analysis of internal auditory canal using CT imaging: An observational study in South Indian adult population - Judica Sheryl; Senthil Ganesh P. Kannappan (MGM Journal of Medical Sciences)
Background: The posterior surface of the petrous part of the temporal bone, located near the anterolateral wall of the posterior cranial fossa, houses the internal auditory canal (IAC). The lateral fundus of this canal is divided into three distinct openings that accommodate the facial, cochlear, and vestibular nerves. The present study attempts to measure the dimensions of the IAC using digital image processing to understand how anatomical variations may aid in surgical planning. Materials and Methods: A morphometric analysis of the IAC was conducted at Saveetha Medical College and Hospital in Chennai, Tamil Nadu, India, from November 2021 to May 2022. The study included subjects aged between 25 and 86 years who underwent temporal computed tomography (CT) scans revealing characteristics of the IAC. Imaging was obtained from the supraorbitomeatal plane with the subjects in a designated head support position. The scans were performed using a Philips Secura™ 128-slice Ingenuity CT scanner. The study measured the IAC opening width (OW), longitudinal length (LL), and anteroposterior (AP) diameter in both male and female subjects. Results: Of the 70 cases included in the study, 27 were female, and 43 were male. Three distinct shapes of the IAC were identified across both genders: cylindrical, funnel-shaped, and bud-shaped. Among the 70 samples, 30 exhibited a cylindrical shape, 29 were funnel-shaped, and 11 were bud-shaped. The mean width of the IAC (OW) for both male and female subjects was 0.77 ± 0.19. The mean LL was 1.08 ± 0.20 in males and 1.02 ± 0.21 in females. The mean AP diameter was 0.44 ± 0.13 in males and 0.40 ± 0.13 in females. Conclusion: A detailed understanding of the anatomy and spatial relationships within the IAC is critical for diagnosing and treating conditions affecting this region. This space’s frequent vestibular schwannomas (auditory neuromas) underscores the canal’s clinical significance.